Management Practices, Worker Commitment, and Workplace Representation - John T. Addison; Paulino Teixeira (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Using multilevel mixed effects ordered logistic models, this paper conducts an original investigation of the new management as a technology approach for all EU nations in a framework that explicitly recognizes worker representation while incorporating the notion of affective commitment. It is reported that that low worker commitment is unlikely to be found in establishments with better management practices and that, controlling for management practices and worker representation, the hypothesis that financial and productivity performance is superior in establishments without worker representation is not rejected by the data. For establishments with worker representation, the works council-only variant is seemingly the most favorable regime for financial performance, although this does not carry over to the labor productivity outcome. On net, however, the evidence suggests that the selected management practices are likely to be favorable to performance in plants with and without formal workplace representation. Greater worker commitment is strongly associated with improved labor productivity. Moreover, in this case there is seemingly no difference between works council-only representation and no representation at all. Overall, although the results for workplace representation and the financial situation are mixed, it is the case that greater commitment trumps any negative influence of worker representation type.
Keywords: D22; J53; J50; L20; M54; 330; management as a technology; human resource management; worker commitment worker representation; labor productivity; financial performance